THE RELATIONSHIP BETWEEN LOCAL GOVERNMENTS AND NON-GOVERNMENTAL ORGANIZATIONS IN PROMOTING LOCAL DEVELOPMENT AND SOCIAL WELFARE (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the dynamic relationship between local governments and non-governmental organizations (NGOs) in advancing local development and social welfare. Local governments are essential in setting policies, providing public services, and ensuring the well-being of citizens. NGOs, on the other hand, play a crucial role in filling gaps, providing specialized services, and advocating for marginalized populations. Through collaborative efforts, these two entities can complement each other's strengths to enhance community resilience and improve the quality of life. This paper examines case studies from various regions, analyzing how local governments and NGOs have partnered to address issues such as poverty, healthcare, education, and environmental sustainability. The study identifies the key factors that contribute to successful partnerships, including clear communication, resource-sharing, and mutual trust. However, challenges such as conflicting priorities, limited resources, and accountability issues are also discussed. The paper concludes with policy recommendations to strengthen the collaboration between local governments and NGOs for sustainable development and social welfare.